Molecular simulation of shale gas adsorption in type III kerogen organic matter. (17th December 2022) - Zhang, Jizhen; Han, Denglin; Wang, Chenchen; Lin, Wei; Zhang, Huiwen; Li, Shuo
Abstract: Type III kerogen play an important role in coal-bearing shale gas generation and occurrence. The physical and structural properties and the adsorption mechanism of kerogen are difficult to be analyzed comprehensively by experiments. Molecular simulation provides technical support to the investigation of the adsorption and enrichment mechanisms of shale gas at molecular level. Using the Grand Canonical Monte Carlo (GCMC) and Molecular Dynamic (MD) methods, type III kerogen model was constructed, and the adsorption behaviors of methane were investigated. The effects of temperature and gas composition on shale gas adsorption, and the adsorption selectivity of mixed gas C2 H6 /CH4 and the radial distribution function (RDF) were also discussed. The results show that the adsorption capacity of C2 H6 decreases with the increase of temperature and pressure. The adsorption capacity of C2 H6 increases first, then decreases, and finally tends to be stable. The adsorption experiment and molecular simulation results show that Type III kerogen has a stronger adsorption capacity for C2 H6 than CH4 . C2 H6 in smaller nano-scale pores are more difficult to desorption under the lower pressure. The carbon atoms in kerogen interact strongly with the gas molecule of CH4 and C2 H6 .